2014
DOI: 10.1016/j.bone.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-1 is required for bone formation and Bmp-2-mediated induction of Osterix

Abstract: The extracellular matrix protein Fibulin-1 (Fbln1) has been shown to be involved in numerous processes including cardiovascular and lung development. Here we have examined the role of Fbln1 in bone formation. Alizarin red staining of skulls from Fbln1 deficient mice showed reduced mineralization of both membranous and endochondral bones. Micro CT (μCT) analysis of the calvarial bones (i.e., frontal, parietal and interparietal bones collectively) indicated that bone volume in Fbln1 nulls at neonatal stage P0 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
(67 reference statements)
2
20
0
Order By: Relevance
“…As determined by qRT‐PCR analysis, the expression of these genes was consistent with the dataset (Figure B and C). Previous studies have reported several of the above‐mentioned genes (CIDEC, MAOA, SAA1, SVEP1, FBLN2, ADARB1, ZBTB16, ANGPT1, FBLN1, FZD4, OMD, ABI3BP, RGS4, CXCL8) are closely related to bone homeostasis and the process of osteogenic differentiation, and these studies further supported the reliability of the dataset. To identify the BMSCs osteogenic differentiation‐related genes, we chose 10 of the other upregulated genes, namely EFHD1, FKBP5, APOD, ACTC1, SORT1, COMP, CLEC3B, CRYAB, WASF3, LMOD1, and downregulated their expression by specific siRNA in BMSCs (Figure D‐M).…”
Section: Resultssupporting
confidence: 72%
“…As determined by qRT‐PCR analysis, the expression of these genes was consistent with the dataset (Figure B and C). Previous studies have reported several of the above‐mentioned genes (CIDEC, MAOA, SAA1, SVEP1, FBLN2, ADARB1, ZBTB16, ANGPT1, FBLN1, FZD4, OMD, ABI3BP, RGS4, CXCL8) are closely related to bone homeostasis and the process of osteogenic differentiation, and these studies further supported the reliability of the dataset. To identify the BMSCs osteogenic differentiation‐related genes, we chose 10 of the other upregulated genes, namely EFHD1, FKBP5, APOD, ACTC1, SORT1, COMP, CLEC3B, CRYAB, WASF3, LMOD1, and downregulated their expression by specific siRNA in BMSCs (Figure D‐M).…”
Section: Resultssupporting
confidence: 72%
“…32 In this study, the VH or rhBMP-2 release profiles clearly indicated the sustained release of VH or rhBMP-2 from n-MZS, whereas MZS showed an initial burst release. The large amount of VH or rhBMP-2 could be loaded into n-MZS by a physical adsorption process, which could avoid initial burst release of VH or rhBMP-2.…”
Section: Bet Analysissupporting
confidence: 57%
“…Two other fibulin family genes have been reported to regulate TGF-β family signaling. Fibulin-1 regulates BMP signaling through direct binding to BMP-2 (Cooley et al, 2014), whereas Fibulin-3 inhibits TGF-β 1 signaling by interacting with TpRI/ALK-5 to prevent formation of a functional ligand-receptor complex (Tian et al, 2015). Fibulin-4 mutations are associated with patients with aortic aneurysms, arterial tortuosity and stenosis.…”
Section: Discussionmentioning
confidence: 99%